Noticiero Radiofónico Regional Amazónico NUESTRA TIERRA (SHUAR). - Chiluisa Garcés, María José (2016)
“NUESTRA TIERRA” is a radio newsreel driven with intercultural orientation and conducted in Spanish and Shuar-Chicham, both Ecuadorian languages. The initiative is born from the intention to cover necessities related to communication and interaction between different Amazonian peoples. This is made through a product which design bears in mind social features of those peoples, starting with the bilingualism Spanield - Shuar, passing through the themes themselves until the categories for the segments of the show, all of them related to Amazonian cultures in both shape and content. NUESTRA TIERRA has an approximate length of 25 minutes and is broadcasted two times per week, on evening schedule. The contents cover entertainment, culture, general information and varieties. It intends to promote interactions among cultures, diversity and values directly related to coexistence, emphasizing specially on Amazonian peoples, through transmission of information and news, interviews with relevant social characters and a rest of radio newsreel segments, everything framed into the vision of NUESTRA TIERRA.